Dynamic Phosphate Uptake in Arbuscular Mycorrhizal Roots Under Field Conditions - Kobae, Yoshihiro (Frontiers in Environmental Science, 2019)
Many crops are colonized with arbuscular mycorrhizal fungi (AMF), which can efficiently absorb nutrients such as phosphate from the soil. The utilization of mycorrhizal symbioses is one of the most promising options for developing resource-saving and sustainable agricultural systems. Most laboratory studies have illustrated the roles of AM symbiosis by inoculating plants with limited AMF isolates. In the field, however, the roots of crops are co-colonized with multiple AMF species, which are difficult to separate and identify and may have different abilities regarding phosphate uptake. In addition, it is difficult to understand which AMF are functional due to the dynamics of AMF colonization processes and the largely unknown genomic structure. This review summarizes key discoveries supporting the importance of the dynamics of AM colonization and genomic structure, which potentially influence the characteristics of AM phosphate uptake. Moreover, this review aims to identify the research direction necessary to obtain a better understanding of the phosphate uptake systems of crops in the field.